Швейцарський досвід організації навчального процесу на засадах полікультурності у вищій школі - Радченко, Тетяна (Studies in Comparative Education, 2015)
У статті уточнено поняття «полікультурна освіта» в контексті його функціональних зв’язків із категоріями крос-культурної і глобальної освіти; здійснено інтерпретацію понять «полікультурна компетентність», «крос-культурна компетентність», «глобальна компетентність». Визначено сутність організації навчального процесу на засадах полікультурності у вищих навчальних закладах. Охарактеризовано полікультурні засади організації навчального процесу у вищій школі Швейцарії. Звернено увагу на формування полікультурної компетентності як ключової професійної характеристики майбутнього фахівця в умовах сучасного культурно різноманітного суспільства. В статье уточнено понятие «поликультурное образование» в контексте его функциональных связей с категориями кросс-культурного и глобального образования; осуществлена интерпретация понятий «поликультурная компетентность», «кросс-культурная компетентность», «глобальная компетентность». Определена сущность организации учебного процесса на принципах поликультурности в высших учебных заведениях. Охарактеризованы поликультурные основы организации учебного процесса в высшей школе Швейцарии. Обращено внимание на формирование поликультурной компетентности как ключевой профессиональной характеристики будущего специалиста в условиях современного культурно разнообразного общества. The concept of «multicultural education» in the context of its functional links with the categories of cross-cultural and global education as well as interpretation of the definitions «multicultural competence», «cross-cultural competence» and «global competence» are defined in the article. Multicultural fundamentals of organization of studies at universities have been determined. The article considers Swiss system of higher education as a multicultural phenomenon. Operation of the universities meets the requirements and takes into account equal educational opportunities for members of all ethnic groups of the country, attracts foreign students and encourages academic mobility. The essence of organization of studies on the multicultural fundamentals at higher education institutions has been characterized. The research emphasizes the multicultural fundamentals of organization of studies at Swiss universities which are manifested by meaningful signs of multiculturalism for the selected components related to target, content, operation, economic resources, human resources, student contingent, structure and monitoring. The signs of multiculturalism include promotion of humanization, democratization, diversification, internationalization, multilingualism, openness and accessibility of education. Great attention is paid to the formation of multicultural competence as a key professional characteristic of the prospective expert under conditions of the modern culturally diverse society.